'Let's talk about sex': the state of gender in IORA for a future agenda. Issue 2 (4th May 2018) - Kotze, Joleen Steyn; Bohler-Muller, Narnia
ABSTRACT: Gender equality is high on the global agenda. With the adoption of the sustainable development goals, the world reaffirmed its commitment to advance gender equality and the empowerment of all women and children. In this context, the Indian Ocean Rim Association (IORA) committed itself to gender equality through advancing women's economic empowerment [IORA (2016). Declaration on gender equality and women's economic empowerment . Retrieved fromhttp://www.iora.net/media/168553/iora_declaration_on_gender_equality_and_women_s_economic_empowerment_2016.pdf ]. At the heart of sustainable development for the IORA countries is the need for women's economic empowerment. Drawing on the United Nations Development Programme's 2016 Human Development Report Statistical Annex and the World Bank's report [(2016). Women, business and law index . Retrieved from http://wbl.worldbank.org/data/exploretopics/protecting-women-from-violence], this paper presents a baseline analysis of gender, transformation, and development within the IORA. The paper analyzes gender and transformation within IORA focusing on policy directives for gendered development and transformation. We argue to advance gender transformation within IORA, a political imaginary of what a gender-equal IORA entails is an essential component of gendered developmental policy within the region. This requires building transnational feminist and women empowerment networks to create discursive feminist frameworks that guide women empowerment and gender justice within IORA, contributing to a transformed understanding of diplomacy within the region.